EFFECTS OF S(+)-KETAMINE CONTINUOUS RATE INFUSION IN HORSES ANESTHETIZED BY HALOTHANE - Borges, José Henrique Saraiva (2010)
The horse’s blood pressure is susceptible to changes induced by volatile anesthetics. Because of that, the use of anesthesic techniques which keep stable the horse´s blood pressure is essencial. Ketamine is an important induction and maintenance anesthetic agent used in the horse anesthesia practice mainly to improve the blood pressure. S(+)-ketamine provides the same effects on the blood pressure, with greater analgesic results and less side effects than the normal ketamine. Although some studies have been conducted with ketamine continuous rate infusion during the halothane anesthetized horses, the S(+)-ketamine has not been evaluated yet. Considering the increased use of ketamine, it is important to evaluate its cardiovascular and respiratory effects in halothane anesthetized horses. To conclude, S(+)-ketamine 0.01mg/kg/min. continuous rate infusion did not induce additive cardiovascular and respiratory depression in halothane anesthetized horses.KEY WORDS: S(+)-ketamine, horses, halothane, continuous rate infusion.